Why Experienced Incivility Triggers Instigated Incivility: Combining the Affect-based and Resource-based Pathways - Peng, Xin (2020)
Ever since Andersson and Pearson's seminal work (1999), incivility has become one of the most commonly studied forms of mistreatment in the organizational sciences (Hershcovis, 2011). While research to date has yielded significant findings about the effects of experienced incivility, far less is known about the underlying mechanisms that linked experienced incivility and instigated incivility. Among the limited studies investigating the positively relationship between experienced incivility and instigated incivility, two distinct theoretical frameworks, affective-based perspective and resource-based, were drew upon. And these two perspectives have never been examined in the same model. To this end, I investigated negative affect (affect-based mechanism) as well as rumination and mental fatigue (resource-based mechanism) as parallel mediators of the relationship between experienced incivility and instigated incivility. I also examined the moderating role of hostile attribution bias in the first stage of the parallel mediation. Using longitudinal design, the current study supported only the affect-based pathway but not the resource-based one. The study also found surprising results regarding the role of hostile attribution bias. Implications and future directions were discussed